Lessons learnt from syphilis-infected blood donors: a timely reminder of missed opportunities. (11th August 2021) - Harvala, Heli; Reynolds, Claire; Fabiana, Alvin; Tossell, Joanne; Bulloch, Gillian; Brailsford, Susan; Blackmore, Stuart; Pomeroy, Louise
Abstract : Objective: Due to the increased number of syphilis infections diagnosed in the UK and beyond, we reviewed our data on blood donors infected with syphilis in the UK and Ireland between 2016 and 2019. Methods: Data were extracted from the surveillance database for all blood donors confirmed positive for syphilis in the UK and Ireland between 2016 and 2019, together with the total number of donations tested during that period. Data on positive cases included gender, age group, reported treatment, symptoms and confirmatory results. All cases were divided into recently acquired within 24 months and past syphilis infection. We also reviewed the information on symptoms characteristic of syphilis reported by blood donors with an untreated syphilis infection during the postdonation discussions. Results: Screening of 8 246 600 blood donations for treponemal antibodies identified 316 blood donors with confirmed syphilis infection in the UK and Ireland between 2016 and 2019 (1.6 per 100 000 donations). 42% of them (133 of 316) were classed as a recent infection based on their donation testing results, previous donation date and clinical history provided, and they were hence considered potentially infectious. Most of these blood donors (202 of 316, 64%) had not been previously diagnosed or treated for syphilis, although 50 of them reported symptoms consistent with syphilis infection and 19 had been misdiagnosed despite seeking medical help. Conclusions: This observational study shows that syphilis infection remains undiagnosed, especially among heterosexual men, and that infectious syphilis is often missed as a differential diagnosis even when donors have presented with genital or oral ulceration, rashes in the genital area and lymphadenopathy. Considering the recent resurgence of syphilis infections in the UK and beyond and our generally expanding sexual networks, it is important to consider syphilis in differential diagnosis even if specific risk factors have not been identified.